The Christmas Lamb - Olsen, Ole J. (My University, 1907)
Introduction: The sheep industry in Kansas is the least advanced of any of the common branches of animal husbandry. Why this should be so hardly explains itself, except that the country is comparatively new and we have not yet reached the stage of intense farming. Sheep are about the most profitable of all domestic animals if handled right. They have always found a ready market and prices have been very good in recent years. They are a very economical animal, making good use of their food, are easy to keep and will live on a large variety of feeds and even on plants which no other animal will touch. The Iowa Station has found that out of the five hundred nineteen weeds and grasses in the Mississippi valley, sheep will eat four hundred eighty or nearly four times as many as any other domestic animal will eat. But this is not all; they are great helpers in building up the soil, their manure being very rich and valuable. We see that general sheep farming is uncommon in this state, but there is a phase of it which is still more uncommon; in fact it is almost rare; this is the raising of the "Chirstmas Lamb". This branch of sheep farming is comparatively new to us and it is only successful near large centers of wealth where we find people who care more for satisfying their appetites than they do for money. Up till recently the center of wealth has been on the eastern coast, but now it is steadily moving westward and with it the raising of the Christmas Lamb will also move. In the large eastern cities the demand for this class of lambs is almost unlimited, and more, their popularity is steadily increasing. People consume more sheep now than ever before. New York City is a good example, seventy thousand being consumed there weekly. Up till recently New York was the only market for this class of lambs, but now we find a demand for them in all of our western cities, which, although limited, is steadily growing.
Citation: Olsen, Ole J. The Christmas Lamb. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: The Christmas Lamb; Sheep Industry; Animal Husbandry; Raising Sheep in Kansas; Sheep Consumption; Theses